Influence of coffee packaging on consumer purchase decision - Silva, Hélio Andreja dos Reis; Pereira, Rafaela Corrêa; Marques, Clara Suprani; Graciano, Amanda Camilo (Seven Editora, 2024)
Packaging, aside from its primary role in containing food products, serves the crucial function of shaping expectations for a brand or product through its visual appeal, significantly influencing purchasing decisions. In the context of coffee, this has gained heightened relevance given the evolving market dynamics and the increased emphasis on the product’s positioning and differentiation in recent years. This study aimed to identify the key elements consumers prioritize when evaluating coffee packaging and examine the impact of both packaging and labels on the purchasing decisions of consumers. Through the administration of questionnaires (n = 100), the research revealed that color choices significantly influence consumer attraction, with red, dark brown, orange, and black standing out as particularly captivating options. The study also noted a substantial receptivity to innovative packaging, featuring distinctive graphic or technological elements. Conversely, aspects such as packaging format, ergonomics, vacuum/QR Code technologies, and packaging material demonstrated limited discernible impact on consumer preferences. The findings not only offer valuable insights for coffee-producing companies seeking to standardize packaging based on consumer preferences but also contribute to future research endeavors. By uncovering factors that may not resonate with consumers, this study lays the groundwork for further inquiries and the validation of hypotheses within the realm of coffee packaging research. DOI:https://doi.org/10.56238/sevened2023.001-006